(3GdJYhjV GdfbOj dQUjO GdELGRGJ GdEYJjGOjI HYO GfJgGA GdNOeI (B/s - (3ehSi, YHO GdZaGQ GHQGgjes ((3GdbGgQI(B: s (3OGQ GdcJH GdbGfhfjI(B, s, 2001)
(3GdgOa ef GdELGRGJ hCfhGYgG heYfi GdJYhjV GdfbOj(B- (3hXGFa GdeSJMbjf ddJYhjV(B- (3efGW GdESJMbGb ddJYhjV(B- (3TQhW GSJMbGb GdJYhjV(B- (3GdGTNGU GdeSJMbjf dbjeI GdJYhjV Yf QUjO GdELGRGJ GdEYJjGOjI(B- (3cjajI MSGH GdJYhjV(B- (3JbGOe GdMb aj GdJYhjV(B- (3GdeMceI GdeNJUI hGdELQGAGJ GdJWHjbGJ GdbVGFjI ddCMcGe hGdaJGhi(B.s
Keywords: (3GdJYhjV GdfbOjs; (3bGfhf GdYeds